Alternative foraging strategies in a wild population of tits (Paridae) - Milligan, N (2015)
How individual animals divide their time between activities such as feeding, predator vigilance, resting, and interacting with conspecifics reflects trade-offs between different fitness related traits (e.g. starvation avoidance, predator avoidance or reproductive performance). Time allocated for foraging to meet energy requirements forms an essential component of animals’ daily time budgets. Furthermore, individuals vary in state and the environment they experience, which will influence how they prioritize and organize different behaviours – the dynamics of which may be affected by processes acting at different timescales. Small animals with high metabolic rates must feed frequently each day, enabling fine control of the precise timing of feeding. However, little is known about how fine temporal-scale variation in individual behaviour scales up to shape daily routines, or what the consequences of inter- and intra-individual differences in this process may be. The main objective of this thesis was to investigate the causes and consequences of individual variation in the foraging behaviour of wild great tits (Parus major) and blue tits (Cyanistes caeruleus) visiting artificial feeders during winter, ranging in temporal scale from single feeder visits to seasonal shifts in behaviour. First, I described a novel axis of individual variation in how individuals distribute their feeder visits across the day. This captured the extent to which single feeding events were clustered into foraging bouts, with ‘binge-eaters’ and 'grazers' at either end of a continuous spectrum. This axis (level of binge-eating) described 38% of individual variation in observed feeder behaviour and was repeatable within individuals both within and across seasons. Dominance-related factors (species, age and sex) and territorial location predicted inter-individual differences. Individuals exhibited some flexibility in their foraging strategy in relation to local competition, binge-eating more when feeders were quieter than their average experience. The abiotic environment also influenced feeding patterns; birds clustered their feeding behaviour more tightly within a day as day length decreased in midwinter, while visiting feeders more frequently overall on colder days. I then demonstrated that individuals can vary both in overall foraging behaviour, and in their susceptibility to interference, with subordinate individuals responding more negatively to an increase in competition. An experimental manipulation revealed that interference competition at feeders can reduce foraging efficiency. Next, by incorporating a social network approach, I showed that great tit foraging strategies were related to patterns of social interaction and were non-randomly distributed across the social network. This positive assortment indicated a link between foraging behaviour and social structure, likely due to positive feedback. Finally I found evidence that social bonds influence foraging behaviour: pairs of great tits that subsequently bred together exhibited similar foraging strategies, but only after pair formation, suggesting convergence of foraging behaviour. This thesis represents the first investigation of individual differences in high temporal-resolution patterns in foraging behaviour in a wild population, carried out across multiple years. The work emphasizes the importance of monitoring individual behaviours at appropriate timescales and relating these measures to relevant processes, e.g. pair formation. The results presented here demonstrate how fine-scale behavioural differences can influence how: individuals cope with a changing environment, interact with other individuals in a group context, and shape social structure which can then feed back to impact on individual behaviour. The interaction of these behavioural processes may have consequences for fitness, population dynamics and community composition.